Implementation of the Road Agency Policy as a Parking Area for Kayutangan Heritage Malang City - Indiati; Lita Juniati; Suryo Hartoko Minarwanto (Jurnal Administrasi Pemerintahan Desa, 2025)
The Kayutangan area in Malang City is one of the cultural heritage areas that has historical value and is synonymous with the architecture of interesting old buildings. However, currently the area faces challenges related to the use of the road body as an extensive vehicle parking area. This can damage the beauty and authenticity of the cultural heritage area of Malang City. This study uses Campbell's theory of effectiveness which states that effectiveness measurement includes program success, target achievement, satisfaction, input and output levels, and overall goal achievement. The purpose of this study is to identify and analyze the use of road bodies as parking areas in the Kayutangan Area, as well as their supporting and inhibiting factors.  This research method uses a qualitative descriptive approach with data collection through interviews, observations, and documentation studies. The informants in this study are the chief coordinator of EKOSDA Malang City, transportation service partners, the people of Kayutangan Tourism Village, tourist visitors, businessmen, and parking attendants. The results of the study show that the Malang City Government has issued a policy related to the use of road bodies as parking areas, but its implementation has not been optimal, causing the policy to be ineffective and requires follow-up actions.